2005
DOI: 10.1016/j.injury.2004.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Photomessaging in orthopaedic trauma

Abstract: PurposeTo assess the efficacy and usefulness of photo messaging in orthopaedic surgery, specifically in the assessment of trauma radiology. MethodsProspectively, 100 sets of X-rays from patients presenting to our emergency department with a clinical hip fracture were collected. Digital images of these AP pelvis X-rays were taken using a Panasonic GD87 mobile picture-messaging phone ( Fig. 1) by one of the authors using a standard technique. These images were then blindly assessed by two orthopaedic surgeons fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As per the guidelines of American College of Radiology, for teleradiology, a minimum resolution 2000 × 2000 pixels is required for the diagnosis of subtle skeletal disorders such as fractures with only disruption of trabecular pattern [ 8 ]. This requirement encompasses all radiology from X-Rays to mammograms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As per the guidelines of American College of Radiology, for teleradiology, a minimum resolution 2000 × 2000 pixels is required for the diagnosis of subtle skeletal disorders such as fractures with only disruption of trabecular pattern [ 8 ]. This requirement encompasses all radiology from X-Rays to mammograms.…”
Section: Discussionmentioning
confidence: 99%
“…reviewed 59 patients to assess diagnostic accuracy of teleconsultation using MMS [ 9 ] and found a misdiagnosis rate of 40%, over diagnosis rate of 12%, under diagnosis of 27% and concluded that teleconsultation via MMS demonstrated good reliability but poor diagnostic accuracy using a camera phone with a 1.2MP camera and screen resolution of 176X208. In existing literature, the resolution of the images and the screen quality formed the bottleneck in using MMS of radiographs as a diagnostic tool [ 8 ].…”
Section: Introductionmentioning
confidence: 99%